Kajian terhadap Dampak Short Video melalui Studi Kasus Kampanye Nuvo Family Lawan Brain Rot - Mey Shity Ruspadilah; Wiwi Isnaini (Studia : Journal of Humanities and Education Studies, 2026)
The development of digital content on social media has changed the way people consume information. Short-form digital content, which is instant and tends to be hyperbolic, has the potential to affect attention span and thinking ability. This phenomenon is commonly referred to as Brain Rot, a condition characterized by decreased concentration and cognitive ability due to repeated exposure to short digital content. This study aims to examine the NUVO Family Fight Brain Rot, Let's Play Outside campaign as an educational campaign to raise public awareness of the negative impacts of excessive short-form digital content consumption. This study employed a qualitative approach using descriptive analysis through a case study of the campaign. Data were collected through observations of visual messages, narrative patterns, and communication strategies presented in the campaign. The findings indicate that the NUVO Family campaign can be categorized as an Ideologically/Cause-Oriented Campaign that applies visual communication strategies, social marketing, and parenting education to encourage behavioral change. The campaign not only encourages children to engage in outdoor activities but also increases parents' awareness of the importance of balancing digital media use with physical activities as an effort to reduce the negative impacts of excessive short-form digital content consumption.